Design and Development of the “PETUALANGAN AKSA” Game as Javanese Alphabet Introduction Media - Rozan, Hanan Syafial; Padmasari, Ayung Candra; Nurhidayatulloh, Nurhidayatulloh (Jurnal Pendidikan Multimedia (Edsence), 2023)
Javanese script is one of the materials in Javanese language subjects that begin to be studied at the elementary school level. In SDIT Bina Insan Kamil Sidareja there are still many students who do not understand and have difficulty in learning Javanese characters.  Factors that influence students' difficulties in learning Javanese characters are because students very rarely intersect with Javanese characters in everyday life. Teachers have not used learning media that can attract the attention of students. Overcoming these problems, researchers used the Luther-Sutopo version of the Multimedia Life Development Cycle (MDLC) development model in making the Aksa Adventure game as a medium for introducing Javanese script in Grade 4 SDIT Bina Insan Kamil Sidareja. The purpose of this study was to design the game "Petualangan Aksa" and test the feasibility of the game "Petulangan Aksa" as a medium for introducing Javanese script for grade 4 students at SDIT Bina Insan Kamil Sidareja. The benefits of research are to know the stages of making games and to know the feasibility of media as an introduction to Javanese script at SDIT Bina Insan Kamil Sidareja. After alpha and beta testing, the results of the "Petualangan Aksa" game research obtained a score of 97.14% for the material validation test, 88.77% for the media validation test and 88.54% for the beta test so that it was very feasible to use. The conclusion of the study is that researchers have successfully designed the game "Petualangan Aksa" as a media for introducing Javanese characters at SDIT Bina Insan Kamil Sidareja.